Strengthening Security and Sovereignty: Madagascar's Defense Diplomacy with China for Capacity Building - Gea Avanantsoa, Harlette Naudy; Mahroza, Jonni; Montratama, Ian (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Madagascar's strategic partnership with China aims to enhance its defense capabilities. Given its strategic location and limited resources, Madagascar has increasingly relied on defense diplomacy to build a robust defense industry. This collaboration leverages China's extensive experience in defense industry development. The main question that the researcher answers in this paper is «how Madagascar navigates the complex geopolitical landscape to cultivate a homegrown defense industry with China's support». The researcher employs qualitative methods, including case studies, policy analysis, and stakeholder interviews, to examine the historical context, strategic goals, and implementation of defense diplomacy. Key objectives include military modernization, developing a local defense industry, and improving security. The cooperation involves military aid, training and industrial cooperation. Despite challenges such as dependency risks and geopolitical tensions, the partnership has resulted in significant benefits, including enhanced military capabilities and economic development. The paper highlights the importance of strategic planning, effective implementation, and balanced international relations. This study underscores the critical role of defense diplomacy in achieving national security and development goals for small nations like Madagascar.